2005
DOI: 10.5194/acp-5-2299-2005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of aerosol particle episodes in Finland caused by wildfires in Eastern Europe

Abstract: Abstract. We studied the sources, compositions and size distributions of aerosol particles during long-range transport (LRT) PM 2.5 episodes which occurred on 12-15 August, 26-28 August and 5-6 September 2002 in Finland. Backward air mass trajectories, satellite detections of fire areas and dispersion modelling results indicate that emissions from wildfires in Russia and other Eastern European countries arrived in Finland during these episodes. Elemental analyses using scanning electron microscopy (SEM) couple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 40 publications
4
28
0
Order By: Relevance
“…Sufficient data on PM 10 are now available worldwide that emphasize on characteristics and sources (Kyotani and Iwatsuki 2002;Shi et al 2003;Dan et al 2004;Samburova et al 2005;Johnson et al 2006), particle size distribution (Chonga et al 2002;Han et al 2005), and spatial and temporal patterns (Gomiscek et al 2004; Anttila and Salmi 2006). Some studies reported the emissions of fine particles caused by natural episodes (Niemi et al 2004(Niemi et al , 2005Wang et al 2006). Nowadays, in developed countries, attention has been paid to fine and ultrafine particles.…”
Section: Introductionmentioning
confidence: 99%
“…Sufficient data on PM 10 are now available worldwide that emphasize on characteristics and sources (Kyotani and Iwatsuki 2002;Shi et al 2003;Dan et al 2004;Samburova et al 2005;Johnson et al 2006), particle size distribution (Chonga et al 2002;Han et al 2005), and spatial and temporal patterns (Gomiscek et al 2004; Anttila and Salmi 2006). Some studies reported the emissions of fine particles caused by natural episodes (Niemi et al 2004(Niemi et al , 2005Wang et al 2006). Nowadays, in developed countries, attention has been paid to fine and ultrafine particles.…”
Section: Introductionmentioning
confidence: 99%
“…1 In 2014 alone, the US had 63,612 wildfires and 17,044 prescribed burns with a combined burned area of about 6 million acres, leading the US Department of Interior and the US Forest Service to spend approximately $1.5 billion on suppression efforts. 2 In response to wildland fires increasing in both frequency and intensity in recent years, 3,4 the US Bureau of Labor Statistics estimates that the firefighter employment numbers will also continue to increase in the years to come.…”
Section: Introductionmentioning
confidence: 99%
“…Fires in Russia and eastern Europe also influence northern Europe. For example, Niemi et al (2005) showed that increases in very low longterm background PM 2.5 levels of about 8 µg m −3 in parts of Finland were increased to more than 30 µg m −3 during such events.…”
Section: Wildfire Trendsmentioning
confidence: 99%